Dietary phytochemicals alleviate the premature skin aging: A comprehensive review - Harpreet Singh; Y.T. Kamal; Jessica Pandohee; Arun Kumar Mishra; Aritra Biswas; Sourav Mohanto; Arvind Kumar; Sagnik Nag; Amrita Mishra; Mhaveer Singh; Himanshu Gupta; Hitesh Chopra (Experimental Gerontology)
Skin aging, often called as premature skin aging, is the hastened deterioration of the skin resulting from multiple factors, including UV radiation, environmental contaminants, inadequate nutrition, stress, etc. Dietary phytochemicals, present in fruits, vegetables, and other plant-derived meals, have gained interest due to their efficiency to eradicate free radicals and lowering the release of inflammatory mediators which accounts for premature skin aging. Several dietary phytochemicals, i.e., carotenoids, polyphenols, flavonoids, terpenes, alkaloids, phytosterols, etc., exhibited potential anti-oxidant, anti-inflammatory, suppression of UV damage, and promote collagen synthesis. In addition, dietary phytochemicals include sulfur, present in various foods safeguard the skin against oxidative stress and inflammation. Thus, this article delves into the comprehension of various dietary phytochemicals investigated to alleviate the premature skin aging. The article further highlights specific phytochemicals and their sources, bioavailability, mechanisms, etc., in the context of safeguarding the skin against oxidative stress and inflammation. The present manuscript is a systematic comprehension of the available literature on dietary phytochemicals and skin aging in various database, i.e., PubMed, ScienceDirect, Google Scholar using the keywords, i.e., “dietary phytochemicals”, “nutraceuticals”, “skin aging” etc., via Boolean operator, i.e., “AND”. The dietary guidelines presented in the manuscript is a unique summarization for a broad reader to understand the inclusion of various functional foods, nutrients, supplements, etc., to prevent premature skin aging. Thus, the utilization of dietary phytochemicals has shown a promising avenue in preventing skin aging, however, the future perspectives and challenges of such phytochemicals should be comprehended via clinical investigations.